Endometrial hyperplasia: without atypia and with atypia - Maksim A. Sabantsev; Svetlana V. Shramko; Vladimir G. Levchenko; Oleg A. Volkov; Tatyana V. Tretyakova (IP Berlin A.V., 2021)
The article analyzes and presents data for the last 70 years from the PubMed database on endometrial hyperplasia (EH), which is one of the leaders in the structure of gynecological diseases and the main predictor of endometrial cancer (EC). The chronicle of the EH classification is highlighted with a focus on changing the designation and relevance of adenomatous EH. It is shown how the current classification of EH, due to the fact that a large number of synonyms is limited by two options, allows to maximize the reproducibility of the diagnosis, improve the interaction of the obstetrician-gynecologist with the pathologist and reduce the treatment inefficiency. The results of modern studies on the prevalence and risk factors of EH and EC differ from previously accepted ones and destroy the Bohman triad. The risks of EH development with tamoxifen and menopausal hormone therapy are determined. The data of current research methods aimed at the diagnosis of EH and EC are indicated. The differences in etiopathogenesis, prevalence, diagnosis, risk factors for development and progression to the malignant process presented in the review represent two types of EH (without atypia and with atypia) as completely different endometrial diseases included in the same classification.